Tailoring Nitrogen Terminals on MXene Enables Fast Charging and Stable Cycling Na-Ion Batteries at Low Temperature - Xia, Yang; Que, Lanfang; Yu, Fuda; Deng, Liang; Liang, Zhenjin; Jiang, Yunshan; Sun, Meiyan; Zhao, Lei; Wang, Zhenbo (Nano-Micro Letters, 2022)
Sodium-ion batteries stand a chance of enabling fast charging ability and long lifespan while operating at low temperature (low-T). However, sluggish kinetics and aggravated dendrites present two major challenges for anodes to achieve the goal at low-T. Herein, we propose an interlayer confined strategy for tailoring nitrogen terminals on Ti3C2 MXene (Ti3C2-Nfunct) to address these issues. The introduction of nitrogen terminals endows Ti3C2-Nfunct with large interlayer space and charge redistribution, improved conductivity and sufficient adsorption sites for Na+, which improves the possibility of Ti3C2 for accommodating more Na atoms, further enhancing the Na+ storage capability of Ti3C2. As revealed, Ti3C2-Nfunct not only possesses a lower Na-ion diffusion energy barrier and charge transfer activation energy, but also exhibits Na+-solvent co-intercalation behavior to circumvent a high de-solvation energy barrier at low-T. Besides, the solid electrolyte interface dominated by inorganic compounds is more beneficial for the Na+ transfer at the electrode/electrolyte interface. Compared with of the unmodified sample, Ti3C2-Nfunct exhibits a twofold capacity (201 mAh g−1), fast-charging ability (18 min at 80% capacity retention), and great superiority in cycle life (80.9%@5000 cycles) at − 25 °C. When coupling with Na3V2(PO4)2F3 cathode, the Ti3C2-Nfunct//NVPF exhibits high energy density and cycle stability at − 25 °C. Highlights: 1 An interlayer confined strategy to realize the substitution of nitrogen terminals between Ti3C2 MXene layers is proposed. 2 The targeted Ti3C2-Nfunct anode exhibits fast-charging ability and great superiority in cycle life at − 25 °C. 3 Ti3C2-Nfunct not only possesses a lower Na-ion diffusion energy barrier and charge transfer activation energy, but also exhibits Na+-solvent co-intercalation behavior at low temperature.